Novel phase I trial design to evaluate the addition of cediranib or selumetinib to preoperative chemoradiotherapy for locally advanced rectal cancer: the DREAMtherapy trial. (August 2019) - Marti, F.E. Marti; Jayson, G.C.; Manoharan, P.; O'Connor, J.; Renehan, A.G.; Backen, A.C.; Mistry, H.; Ortega, F.; Li, K.; Simpson, K.L.; Allen, J.; Connell, J.; et al.
Abstract: Background: The DREAMtherapy (Dual REctal Angiogenesis MEK inhibition radiotherapy) trial is a novel intertwined design whereby two tyrosine kinase inhibitors (cediranib and selumetinib) were independently evaluated with rectal chemoradiotherapy (CRT) in an efficient manner to limit the extended follow-up period often required for radiotherapy studies. Patients and methods: Cediranib or selumetinib was commenced 10 days before and then continued with RT (45 Gy/25#/5 wks) and capecitabine (825 mg/m 2 twice a day (BID)). When three patients in the cediranib 15-mg once daily (OD) cohort were in the surveillance period, recruitment to the selumetinib cohort commenced. This alternating schedule was followed throughout. Three cediranib (15, 20 and 30 mg OD) and two selumetinib cohorts (50 and 75 mg BID) were planned. Circulating and imaging biomarkers of inflammation/angiogenesis were evaluated. Results: In case of cediranib, dose-limiting diarrhoea, fatigue and skin reactions were seen in the 30-mg OD cohort, and therefore, 20 mg OD was defined as the maximum tolerated dose. Forty-one percent patients achieved a clinical or pathological complete response (7/17), and 53% (9/17) had an excellent clinical or pathological response (ECPR). Significantly lower level of pre-treatment plasma tumour necrosis factor alpha (TNFα) was found in patients who had an ECPR. In case of selumetinib, the 50-mg BID cohort was poorly tolerated (fatigue and diarrhoea); a reduced dose cohort of 75-mg OD was opened which was also poorly tolerated, and further recruitment was abandoned. Of the 12 patients treated, two attained an ECPR (17%). Conclusions: This novel intertwined trial design is an effective way to independently investigate multiple agents with radiotherapy. The combination of cediranib with CRT was well tolerated with encouraging efficacy. TNFα emerged as a potential predictive biomarker of response and warrants further evaluation. Highlights: Novel trial design to evaluate cediranib and selumetinib independently with chemoradiotherapy in patients with locally advanced rectal cancer. The combination with cediranib was well-tolerated and efficacious with 41% of patients achieving a pathological or clinical complete response. The recommended phase 2 dose of cediranib is 20 mg/OD. The maximum tolerated dose of selumetinib was not established because of toxicity. Tumour necrosis factor alpha is a potential predictive biomarker, with significantly lower pre-treatment levels in patients that had an excellent response to treatment.